A buzz is part of a bee - Lunn, Carolyn; Dunnington, Tom (Chicago : Childrens Press, 1990)
Enumerates a series of words and the greater things of which they are a part, such as leaf and tree, elbow and arm, candle and cake, and tail and kite.
School Library Journal.
School Library Journal, February 2000.
1.7
2.
K-3
P-2.
Keywords: Vocabulary -- Juvenile literature; Vocabulary; Vocabulary; Readers (Elementary).